Modelling of impact on sandwich structure for fast maintenance loops - Castanie, Bruno; Aminanda, Yulfian; Schwob, Cyrille (2012)
In the aeronautical field, sandwich structures are widely used for secondary structures like flaps or landing gear doors. The modeling of low velocity/low energy impact, which can lead to a decrease of the structure strength by 50%, remains a designer’s main problem. Since this type of impact has the same effect as quasi-static indentation, the study first focuses on the behavior of honeycomb cores under compression. A phenomenological analysis was conducted which highlights the postbuckling behavior of the honeycomb structure thus enabling a discrete modeling. This discrete approach accurately predicts the static indentation on honeycomb core alone, the indentation and the residual dent depth on sandwich structure with metal skins supported on rigid flat support. The domain of validity of this approach is investigated. In any case, the spring elements used to model the honeycomb cannot take into account the transverse shear that occurs in the core during the bending of a sandwich. To overcome this strong limitation, a multi-level approach is proposed. Thus, it is possible to predict the dynamic structural response in the case of low-velocity/low-energy impact on metal-skinned sandwich structure in bending. A good correlation with dynamic experimental tests is achieved. This model is then used to simulate the response of this indented structure subjected to lateral compressive loading (known as CAI/ Compression after impact). A good correlation with test results is obtained except for the very small residual print depth. To predict the residual strength of impacted sandwich, a core crush criterion is proposed and validated first with metallic skins and then with composite skins.